Pengaruh Faktor Risiko Ibu dengan Kejadian Stunting Pada Balita 0-59 Bulan di Desa Penda Asam Wilayah Kerja UPTD Puskesmas Kalahien Kabupaten Barito Selatan Tahun 2023 - Lestari, Pratiwi Puji; Oktaviani, Widia; Amalia, Rizki; Fitriasih (INVOLUSI: Jurnal Ilmu Kebidanan, 2024)
Background The problem of stunting has the potential to hinder children's physical, mental growth and status, so it is important that special attention is given to children. Children with stunting have quite large potential if they grow into unhealthy adults. The causal factors that contribute to the high prevalence of stunting are family and household factors, inadequate additional/complementary food, breastfeeding, and infection. Family and household factors are further divided into maternal factors and home environmental factors. Objective: To determine the influence of maternal risk factors on the incidence of stunting among toddlers in Penda Asam Village, the UPTD Working Area of ​​the Kalahien Community Health Center, South Barito Regency in 2023. Methods: The research design used is analytical research. This research design uses case control. The sample size in this study was 160 children under five, of which there were 26 cases and 134 controls. Results: There is an influence of age, parity, pregnancy interval, height, CED on the incidence of stunting in toddlers 0-59 months in Penda Asam Village, Kalahien Public Health Center UPTD Working Area, South Barito Regency in 2023. There is no influence of education level on the incidence of stunting in toddlers aged 0-59 months in Penda Asam Village, the UPTD Working Area of ​​the Kalahien Community Health Center, South Barito Regency in 2023. Conclusion: Provide education or counseling to mothers with toddlers and prospective mothers during posyandu or classes for pregnant women so that toddlers avoid stunting.